Design, synthesis, and biological evaluation of novel androst-17β-amide structurally related compounds as dual 5α-reductase inhibitors and androgen receptor antagonists. (1st January 2019) - Lao, Kejing; Xun, Guoliang; Gou, Xingchun; Xiang, Hua
Abstract: Prostate cancer (PCa) is the second leading cause of death in men. Apart from androgen receptor, 5α-reductase has also been recognized as a potential target. In this study, a series of androst-17β-amide compounds have been designed and synthesized targeting both AR and 5α-reductase. Their anti-proliferation activities were evaluated in AR + cell line 22RV1 and AR − cell line PC-3. The results indicated that most of the synthesized compounds inhibited the testosterone-stimulated cell proliferation with good selectivity and safety. Among all the compounds, androst[3, 2-c]pyrazole derivatives (9a–9d) displayed the best inhibition activity comparable with flutamide. Moreover, most of the synthesized compounds displayed good 5α-reductase inhibitory activities with IC50 lower than 1 μM. The docking result of 9d -AR indicated that AR was forced to expands its binding cavity and maintain an antagonistic conformation since the steric hindrance of 9d impeded H12 transposition. Overall, compound 9d can be identified as a potential dual 5α-reductase inhibitor and AR antagonist, which might be of therapeutic importance for PCa treatment.